Analysis of Particulates and SO2 Removal from Coal Combustion Emissions Using Cyclone and Wet Scrubber With Textile Wastewater Feed - Huboyo, Haryono S.; Sudarno, Sudarno (TEKNIK, 2020)
Reuse of wastewater in the industry is mostly accomplished for watering plants. In a closed cycle, however, industrial wastewater can be returned through treatment to save water usage. This study aims to analyze textile wastewater's ability to be used as scrubbing liquid in the SO2 gas and particulate removal from coal combustion using a packed wet scrubber. Usually, the textile industry uses boiler fueled by coal and discharging base/alkaline wastewater. The method is carried out experimentally using a prototype device using a combination of cyclone and scrubber, with a source of coal combustion gas emissions. We did experiments using textile wastewater four times and two times using clean water as a control. We monitor the SO2, particulate emission in the gas stream, and pH, sulfate levels, and TSS levels in collected wastewater according to SNI. SO2 gas and particulates from coal combustion will be absorbed by the scrubber's wastewater spray so that SO2 will dissolve into sulfate, particulate matter into TSS. The study results using textile wastewater showed the removal efficiency of particulates on cyclone by 34-78%. Â The removal efficiency of SO2 on wet scrubber was only 24.7%. There was an increase in TSS levels after passing through the scrubber by 46%. The rise in TSS and sulfate concentrations in the wastewater indicates the absorption of SO2 and particulates into wastewater. Based on this result, we can use textile wastewater for controlling the emission of SO2 and particulate from coal combustion by feeding it for the scrubber. However, the efficiency of this process is not optimal.